Peran AVSEC (Aviation Security) Dalam Menunjang Keamanan Navigasi Penerbangan Di Airnav Unit Maumere - Mario Ferdinandus Jeo; Viktor Eko Transilvanus; Yustina Olivia da Silva; Nunsio Handrian Meylano (Universitas Nusa Nipa Maumere, 2026)
This study aims to analyze the role of Aviation Security (AVSEC) and Air Traffic Control (ATC) in maintaining flight safety and security at Frans Seda Maumere Airport and relate it to Operational Management theory. The method used is a qualitative approach through interviews with sources directly involved in airport operations. The results of the study show that AVSEC acts as the first line of defense in the aviation security system through passenger, baggage, and cargo checks (SCP1 and SCP2), as well as surveillance of restricted areas (airside). Meanwhile, ATC is responsible for regulating aircraft traffic in the air and on the ground to ensure smooth and safe flights. The collaboration between AVSEC and ATC can be categorized as a form of integrated operational management, which is the integrated operational management between different units with a common goal, namely to ensure optimal aviation security and safety. Thus, the implementation of structured and integrated operational management is key in supporting the continuity of safe, orderly, and efficient flight operations.